Inuit DLT, Language Management and World Technology - Collis, Dirmid (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractThis article deals with the use of distributed language translation (DLT) to unite the Inuktitut-lnupiaq-speaking world, giving its school diplomas equal value in each Inuit regional language to those in more widely-spoken languages. It discusse: the DLT technique, its economic and procedural advantages; language ecology and what it means to speakers and non-speakers of Inuktitut: the role that technical translation can play in maintaining language rights; what would be the role of the Inuit translator-terminologist if a "right to know" policy were adopted making available technical and scientific knowledge to the Inuit through their language. It suggests that non-cultural translation may be a People's right which ICI could advance at Geneva. Finally it shows how Inuktitut can become as efficient a language vehicle for knowledge as either Hungarian or Japanese, and why.